Tourism – uroboros or Phoenix? Report from the discussion - Makowska-Iskierka, Marzena; Wojciechowska, Jolanta; Agnieszka Gralak (Turystyka – to znaczy co? Uroboros czy Feniks, 2025)
The article explains the significance of the titular symbols of the uroboros and the Phoenix and presents statements from participants in the discussion “Tourism – uroboros or Phoenix?”. This debate was held during the jubilee academic conference XL Seminarium Terenowe „Warsztaty z geografii turyzmu”, which took place in Spała from September 26 to 28, 2024. The debaters offered various definitions of how contemporary tourism should be understood, presenting facts, specific examples, personal experiences, and viewpoints, as well as their justifications.